2019
DOI: 10.1002/celc.201801503
|View full text |Cite
|
Sign up to set email alerts
|

Studying Direct Electron Transfer by Site‐Directed Immobilization of Cellobiose Dehydrogenase

Abstract: Covalent coupling between a surface-exposed cysteine residue and maleimide groups was used to immobilize variants of Myriococcum thermophilum cellobiose dehydrogenase (MtCDH) at multiwall carbon nanotube electrodes. By introducing individual cysteine residues at particular places on the surface of the flavodehydrogenase domain of the flavocytochrome, we are able to immobilize the different variants in different orientations. Our results show that direct electron transfer (DET) occurs exclusively through the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…The cysteine mutant with a surface thiol group made it possible to form stable thioether bonds with maleimide groups via click-chemistry, thereby controlling the orientations of the MtCDH mutant on the electrode surface and revealing efficient electrochemical glucose oxidation. Another example reported by Meneghello and associates clearly indicated that the DET-type bioelectrocatalysis of CDH is highly sensitive to the cysteine residues introduced at particular positions [115]. Experimental results also showed that divalent cations (i.e., Ca 2+ and Mg 2+ ) affect the IET kinetics [23,115].…”
Section: 13 Cellobiose Dehydrogenasementioning
confidence: 86%
See 1 more Smart Citation
“…The cysteine mutant with a surface thiol group made it possible to form stable thioether bonds with maleimide groups via click-chemistry, thereby controlling the orientations of the MtCDH mutant on the electrode surface and revealing efficient electrochemical glucose oxidation. Another example reported by Meneghello and associates clearly indicated that the DET-type bioelectrocatalysis of CDH is highly sensitive to the cysteine residues introduced at particular positions [115]. Experimental results also showed that divalent cations (i.e., Ca 2+ and Mg 2+ ) affect the IET kinetics [23,115].…”
Section: 13 Cellobiose Dehydrogenasementioning
confidence: 86%
“…Another example reported by Meneghello and associates clearly indicated that the DET-type bioelectrocatalysis of CDH is highly sensitive to the cysteine residues introduced at particular positions [115]. Experimental results also showed that divalent cations (i.e., Ca 2+ and Mg 2+ ) affect the IET kinetics [23,115].…”
Section: 13 Cellobiose Dehydrogenasementioning
confidence: 86%
“…For example, Bartlett et al reported on the covalent coupling between a surface-exposed cysteine residue and maleimide groups to immobilize different variants of Myriococcum thermophilum cellobiose dehydrogenase ( Mt CDH) at multiwall carbon nanotube electrodes [ 166 , 167 ] ( Figure 13 E). By placing individual cysteine residues around the surface of the CDH DH domain of the enzyme, they were able to immobilize the different variants with different orientations ( Figure 13 A–D).…”
Section: Different Approaches To Tackle Det Issuesmentioning
confidence: 99%
“…The definition of all used mutants and their abbreviate names can be found in ref. [ 167 ]. (The figure was adopted from ref.…”
Section: Figurementioning
confidence: 99%
“…This elegant method combines controlled orientation of the protein at the electrode for ET, sufficient flexibility for activity, and expected enhanced stability. In the case of cellulose dehydrogenase, 40% of initial electroactivity was recovered after 2 months of storage while the wild type enzyme loses progressively its activity within 20 days [245,246]. In addition, controlled orientation allowed investigating mechanistic aspects of the ET.…”
Section: Engineering Of Enzymes Seeking For Both Enhanced Et Efficiency and Stabilitymentioning
confidence: 99%